VEGFR2 and VEGFA polymorphisms are not associated with an inferior prognosis in Caucasian patients with aggressive B‐cell lymphoma. (22nd October 2020) - Kaddu‐Mulindwa, Dominic; Rosolowski, Maciej; Ziepert, Marita; Regitz, Evi; Assmann, Gunter; Bewarder, Moritz; Held, Gerhard; Pfreundschuh, Michael; Bittenbring, Jörg Thomas
Abstract: Purpose: Previous published data showed an impact of single‐nucleotide polymorphisms in the VEGF A and VEGFR2 genes on the survival of patients with various malignancies, among others diffuse large B‐cell lymphoma (DLBCL). Patients and Methods: We investigated the role of four VEGF‐A and two VEGFR‐2 gene polymorphisms on the outcome of 273 patients with diffuse large B‐cell lymphoma who were treated with R‐CHOP within a prospective, randomized trial of the German High‐Grade Non‐Hodgkin Lymphoma Study Group (DSHNHL). The genomic DNA samples were analyzed using commercial DNA Probes (Applied Biosystems, USA) to detect single‐nucleotide polymorphisms in the VEGF A rs699947, rs1570360, rs2010963, rs3025039 and rs1870377, and rs2305948 in the VEGFR2 receptor. Hundred healthy blood donors served as a control. Results: There was no difference between the SNP allele frequencies in lymphoma patients compared to the control group for all investigated SNPs. None of the investigated SNPs was significantly associated with EFS or OS. After adjusting for the International Prognostic Index risk factors in a multivariate analysis, these results could be confirmed. Conclusion: Single‐nucleotide polymorphisms of the VEGF and VEGFR2 were not associated with a worse outcome in Caucasian patients with DLBCL.